Variational solver for elliptic problems in atmospheric flows - Smolarkiewicz, Piotr K.; Margolin, Len G. (Zielona Góra: Uniwersytet Zielonogórski)
We discuss a conjugate gradient type method - the conjugate residual - suitable for solving linear elliptic equations that result from discretization of complex atmospheric dynamical problems. Rotation and irregular boundaries typically lead to nonself-adjoint elliptic operators whose matrix representation on the grid is definite but not symmetric.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka